Economic effectiveness of fixed-dose combination of alogliptin and pioglitazone in diabetes mellitus treatment - S. К. Zyryanov; I. N. Dyakov (Фармакоэкономика)
Objective: to comparatively assess the weighted average costs associated with the use of alogliptin-pioglitazone combination versus glucagon-like peptide-1 receptor agonists (GLP-1 RAs).Material and methods. A retrospective study involved pharmacoeconomic analysis, including cost-minimization analysis and budget impact analysis, with consideration to the efficacy of the compared therapeutic regimens. Data regarding treatment regimens and safety profiles of the alternatives were obtained from the published results of phase III clinical trials and clinical guidelines. Drug pricing information was derived from the state registry of maximum retail prices and auction results.Results. According to the budget impact analysis, the fixed-dose combination of alogliptin and pioglitazone in the treatment of patients with type 2 diabetes significantly reduces the total costs associated with the administration of hypoglycemic agents and management of concomitant cardiovascular complications. A complete replacement of GLP-1 RAs with the alogliptin-pioglitazone combination in the treatment of 83,582 patients is expected to reduce costs by 42.1% (or by 10,934.5 million rubles) over 3 years. The savings generated from this replacement will enable alogliptin-pioglitazone combination therapy for additional 18,622 patients with type 2 diabetes in the first year and 21,103 patients in subsequent years.Conclusion. The use of alogliptin-pioglitazone combination as an alternative to GLP-1 RAs appears economically justified and reasonable with respect to reducing costs associated with hypoglycemic therapy and treatment of cardiovascular events.